Hepatic DNA Damage Induced by Electronic Cigarette Exposure Is Associated With the Modulation of NAD+/PARP1/SIRT1 Axis - Espinoza-Derout, Jorge (Front Endocrinol (Lausanne), 2019)
The prevalence of electronic cigarette (e-cigarettes) use has rapidly increased worldwide. Use of tobacco products has been associated with DNA damage and metabolic syndrome. Using Apolipoprotein E knockout (ApoE(−/−)) mice on a western diet (WD), a mouse model of non-alcoholic fatty liver disease (NAFLD), we recently demonstrated that nicotine in e-cigarettes activates hepatocyte apoptosis, and causes hepatic steatosis. This study examines the harmful effects of e-cigarettes on the liver with a special emphasis on DNA damage and mitochondrial dysfunction. ApoE(−/−) mice were exposed to saline, e-cigarettes without nicotine or e-cigarettes with 2.4% nicotine for 12 weeks using our newly developed mouse e-cigarette exposure model system that delivers nicotine to mice leading to equivalent serum cotinine levels found in human cigarette users. Mice exposed to e-cigarette (2.4% nicotine) had increased apurinic/apyrimidinic (AP) sites, a manifestation of DNA damage. Additionally, e-cigarette (2.4% nicotine) produced a decrease in NAD+/NADH ratio and increased oxidative stress in hepatic cells, in comparison with saline and e-cigarette (0%). Western blot analysis showed that mice treated with e-cigarette (2.4% nicotine) had increased poly (ADP ribose) polymerase (PARP1) activity associated with reduced levels of Sirtuin 1 (SIRT1). Furthermore, mitochondrial DNA mutations and PTEN-induced kinase 1 (PINK1) were increased in mice treated with e-cigarette (2.4% nicotine). Transmission electron microscopy revealed that hepatocytes of mice treated with e-cigarette (2.4% nicotine) exhibited increased vacuolization of the mitochondria and a reduction in cellular organelles. These results demonstrate the adverse effects of e-cigarettes exposure leading to NAD+ deficiency which may suggest a mechanistic link between e-cigarette-induced hepatic DNA damage and mitochondrial dysfunction.